Assessment of 12 Fish Species in the Northwest Pacific Using the CMSY and BSM Methods - Wang, Yibang; Wang, Yuanchao; Liang, Cui; Zhang, Hui; Xian, Weiwei (Frontiers in Marine Science, 2020)
We assessed 12 marine fish species in the Northwestern Pacific exploited by Japanese fisheries, using published catch time series, CPUE data and the CMSY and BSM methods. The results showed that two stocks were severely depleted, two stocks were outside of safe biological limits, three stocks were overfished, three stocks were recovering, while the other two stocks were in good condition. These results match those of previous research on the status of fish species in the Northwestern Pacific, where overfishing is becoming increasingly apparent. We used the CMSY/BSM assessments as a basis for suggestions to assist in the management and rebuilding of fishery resources in this area.